Kallpachakuy: Coca, drink and cigar as strength and protection in the pilgrimage to Qoyllurit´i - Torres Lezama, Vicente (2020)
The objective of this work is to show the notion that the pilgrims of Qoyllurit´I and Quechua settlers of the Peruvian south have about coca, drink and cigar. The research is based on shared practices, interviews and dialogues with pilgrims, dancers and residents of Cuzco from 2011 to 2019. In this pilgrim experience I learned that coca and drinks such as chichi, beer, brandy, cañazo, among other, are considered force or kallpa because they are able to activate people and encourage them to perform certain actions such as dancing with pleasure, working with enthusiasm and speaking fluently. But they are not limited to the provision of force, but they are also heat providers and protectors of evil spirits, aggressive entities and bad winds. Coca, drink and cigar are intentional and capable of bringing the subjects into action.